Eco-spirituality in the Modern Era: A Study of Ecological Sociology and Social Ecology Theory - Orlando, Henrikus (Journal of Sumatera Sociological Indicators, 2025)
This study examines the phenomenon of ecospirituality in the modern era through the approach of ecological sociology and social ecology theory, focusing on a community that applies the principles of sustainability. In this context, ecospirituality is defined as the integration of spiritual values ​​into sustainable environmental practices. Qualitative research methods are used, including in-depth interviews, participant observation, and case studies to explore how community members carry out eco-spirituality practices in their daily lives. The findings show that spiritual relationships with nature encourage collective action in protecting the environment, preserving local culture, and increasing environmental awareness. Although the community faces challenges from the larger economic system, ecospirituality values ​​prove to be a driver of positive social change and environmental sustainability. This study provides insight into the role of ecospirituality in shaping modern society's behaviour towards the environment and its contribution to addressing the current environmental crisis.